The influence of social isolation during the COVID-19 pandemic on speech and language development in preschool children - Ana Lukić; Bojan Joksimović; Jelena Vidojević; Kristina Drašković; Aleksandar Tanović; Veljko Marić; Nenad Lalović; Vesna Krstović Spremo; Siniša Ristić (Биомедицинска истраживања, 2022)
Speech is a way of communication formed by rhythmic units of syllables, words and sentences, and as such is inherent in man, the only being whose organs and psyche are trained for this process. Delayed speech is defined as a phenomenon in which a child does not start speaking on time, or there are errors in the speech pattern that are not appropriate in relation to a given age. It is known that significant risk factors for the development of delayed speech in preschool children are physical, and most often social and emotional in nature. For the normal development of speech, it is necessary that the child is in a human environment, and therefore the circle of people with whom children come into contact should always be expanded. The aim of this study is to Reviews the existing literature on studies examining the impact of social isolation during the COVID-19 pandemic on preschool children, as well as the speech and language development in preschool children. The recent pandemic of corona virus infection (COVID-19) has led to a state of emergency, quarantine, closure of public institutions, and preschools, kindergartens and schools in 172 countries. These epidemiological measures have led to social isolation and the need for children to learn from home, which has manifested itself in the emergence of difficulties in the development of speech and language. Research has shown that during the pandemic, children spent significantly more time watching television and computer screens than before pandemic, and less in play and physical activity.
Keywords: speech; speech development; social isolation; COVID-19 pandemic; preschool children